Magnetic and spectral signatures of Cerrado soils in the state of Goias, Brazil - Fernandes, Kathleen Lourenco [UNESP]; Ribon, Adriana Aparecida; Marques Junior, Jose [UNESP]; Rabelo de Souza Bahia, Angelica Santoe [UNESP]; Tavares Filho, Joao (Empresa Brasil Pesq Agropec, 2017)
The objective of this work was to estimate the iron oxide contents (hematite and goethite) and to characterize the color and the spectral and magnetic signatures of Cerrado soils in the state of Goias, Brazil. Six Oxisols and one Inceptisol were studied. Spectral and magnetic signatures were determined by diffuse reflectance spectroscopy (DRS) and magnetic susceptibility, respectively. Then, the spectral curves and the second derivative calculations were used to determine hematite and goethite contents, as well as soil color after conversion into tristimulus values. Hematite and goethite contents were also obtained by x-ray diffractometry, and soil color was also defined in the field (Munsell color chart). The values for the isomorphic substitution of iron by aluminum and the degree of redness were also determined. DRS can be used to estimate hematite and goethite contents, as well as the color of Cerrado soils in the state of Goias. The spectral signature can point out the main soil properties related to the contents of organic matter, iron oxides, kaolinite, and gibbsite. The magnetic signature, characteristic of soils rich in iron oxides (hematite and goethite), shows the predominance of pedogenic minerals.
Keywords: diffuse reflectance spectroscopy; goethite; hematite; magnetic susceptibility; Oxisols